KONTRIBUSI SUB SEKTOR PERIKANAN TERHADAP PEMBANGUNAN EKONOMI REGIONAL KABUPATEN KEPULAUAN SANGIHE (Contribution of the Fisheries Sub-Sector to Regional Economic Development in Sangihe Islands Regency) - Arif Ichsan Janis; Wenny Tilaar; Leonardus Ricky Rengkung (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The purpose of this study was to analyzeÂ  the contribution of the fisheries sub-sector to the Gross Regional Domestic Product of the Sangihe Islands Regencys, and whether the Fisheries Sub-sector was the dominant sub-sector to the regional economic development of the Sangihe Islands Regency.The results showed that in average the contribution of the fisheries sub-sector to the regional economic development of the Sangihe Islands Regency was 21.86% annually. This value was much greater than the contribution of other sub-sectors to GRDP. Thus, the Fisheries Sub-Sector was the dominant Sub-Sector of the GRDP of the Sangihe Islands Regency.